Analysis of air mass back trajectories with present and historical volcanic activity and anthropogenic compounds to infer pollution sources in the South Shetland Islands (Antarctica) - Szumińska, Danuta; Czapiewski, Sebastian; Szopińska, Małgorzata; Polkowska, Żaneta (Bulletin of Geography. Physical Geography Series, 2018)
This work analyses atmospheric transport of natural and anthropogenic pollution to the South Shetland Islands (SSI), with particular reference to the period September 2015 – August 2017. Based on data from the Global Volcanism Program database and air mass back trajectories calculated using the HySPLIT model, it was found that it is possible that in the analysed period volcanic pollution was supplied via long-range transport from South America, and from the South Sandwich Islands. Air masses flowed in over the South Shetland Islands from the South America region relatively frequently – 226 times during the study period, which suggests the additional possibility of anthropogenic pollution being supplied by this means. In certain cases the trajectories also indicated the possibility of atmospheric transport from the New Zealand region, and even from the south-eastern coast of Australia. The analysis of the obtained results is compared against the background of research by other authors. This is done to indicate that research into the origin of chemical compounds in the Antarctic environment should take into account the possible influx of pollutants from remote areas during the sampling period, as well as the possible reemission of compounds accumulated in snow and ice.